2018
DOI: 10.1007/s11104-018-3622-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and biochemical effects recorded in the tree root zone – soil memory, historical contingency and soil evolution under trees

Abstract: Background and aims The changing soils is a neverending process moderated by numerous biotic and abiotic factors. Among these factors, trees may play a critical role in forested landscapes by having a large imprint on soil texture and chemical properties. During their evolution, soils can follow convergent or divergent development pathways, leading to a decrease or an increase in soil spatial complexity. We hypothesized that trees can be a strong local factor intensifying, blocking or modifying pedogenetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Furthermore, sedimentological and geochemical observations demonstrated that freshwater–alkaline water mixing as a result of neither forest flooding events (Awramik & Buchheim, 2015) nor spring inputs (Jagniecki et al ., 2021) was requisite for the initiation or accretion of multi‐metre mounds. First, the strata immediately below the giants lack geological evidence for a long‐lived shoreline forest environment, such as root traces, mottling and organic‐rich facies (Pawlik & Samonil, 2018). Second, both the ooid‐based estimates of Ω arag ( ca 2 to 5 throughout deposition) and the prevalence of carbonate precipitates in both shallow and deep‐water facies demonstrated that carbonate production in the Sand Wash Basin did not require a freshwater calcium source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sedimentological and geochemical observations demonstrated that freshwater–alkaline water mixing as a result of neither forest flooding events (Awramik & Buchheim, 2015) nor spring inputs (Jagniecki et al ., 2021) was requisite for the initiation or accretion of multi‐metre mounds. First, the strata immediately below the giants lack geological evidence for a long‐lived shoreline forest environment, such as root traces, mottling and organic‐rich facies (Pawlik & Samonil, 2018). Second, both the ooid‐based estimates of Ω arag ( ca 2 to 5 throughout deposition) and the prevalence of carbonate precipitates in both shallow and deep‐water facies demonstrated that carbonate production in the Sand Wash Basin did not require a freshwater calcium source.…”
Section: Discussionmentioning
confidence: 99%
“…First, the strata immediately below the giants lack geological evidence for a long-lived shoreline forest environment, such as root traces, mottling and organic-rich facies (e.g. Pawlik & Samonil, 2018). Second, both the ooid-based estimates of Ω arag (ca 2 to 5 throughout deposition) and the prevalence of carbonate precipitates in both shallow and deep-water facies demonstrated that carbonate production in the Sand Wash Basin did not require a freshwater calcium source.…”
Section: Accepted Articlementioning
confidence: 99%
“…As suggested by the formation of pit-mound microtopography (i.e., mounds and pits resulting from tree throw and degradation of the fallen tree trunks), this process can modify the hillslope microrelief for hundreds of years. Such effects were observed and analyzed on Hala Długa, the montane meadow close to Mt Turbacz, and in the Turbacz Reserve (Pawlik & Kasprzak, 2018;Pawlik & Šamonil, 2018). In these cases, electrical resistivity measurements and soil analyses showed a significant impact of trees on weathering processes, both within root systems of living trees and places disturbed by tree uprooting (tree throw pits and mounds formed after uprooting).…”
Section: Trees Uprooting Biotransport and Weathering Processesmentioning
confidence: 99%
“…Human and other biological impacts are one example; others may include storms, floods, and fires ( Figure 4). Numerous examples exist of divergent geomorphic evolution due to the persistence and/or growth of local disturbances (see Phillips, 1999Phillips, , 2006bBrunsden, 2001 for syntheses and overviews; Toomanian et al, 2006;Pawlik and Šamonil, 2018; Šamonil et al, 2018 for soil geomorphology examples; Fryirs, 2017 for fluvial examples). The possibility exists that at least some of these features that are new on a local scale may also be novel more generally.…”
Section: Inheritable Variabilitymentioning
confidence: 99%